The silence before Bach = Die Stille vor Bach - Portabella, Pere 1927-; Santos, Carles 1940-2017; Albertí, Xavier 1962-; Pladevall, Tomàs 1946-; Figueras, Montse; Brendemühl, Àlex 1972-; Atkine, Féodor 1948-; Brembeck, Christian 1960- (Second Run, 2021)
"Durch eine Mischung aus historischer Rekonstruktion, dramatischen Szenen und dokumentarischen Sequenzen, erschafft der Film eine spielerische, malerische Interpretation der These, dass Johann Sebastian Bach die Welt mit seinem außergewöhnlichen Gehör für Harmonien verändert hat." [amazon.de]
Original: Spanien 2007
special features: presented from the new High Definition transfers, approved by director Pere Portabella ; an in-depth interview with Pere Portabella ; discussing both films, produced by the acclaimed Catalan TV arts programme 'Sala 33' ; 20-page booklet featuring writing on both films by Pere Portabella and Marcelo Expósito ; "The silence of Bach" presented in 5.1 DTS-HD master audio and 2.0 stereo LPCM ; world premieres of both films on Blu-Ray
Bildformat 1.85:1
Keywords: Film; Blu-Ray-Disc